2010
DOI: 10.1063/1.3318262
|View full text |Cite
|
Sign up to set email alerts
|

Tunable self-organization of nanocomposite multilayers

Abstract: In this letter we report the controlled growth and microstructural evolution of self-assembled nanocomposite multilayers that are induced by surface ion-impingement. The nanoscale structures together with chemical composition, especially at the growing front, have been investigated with high-resolution transmission electron microscopy. Concurrent ion impingement of growing films produces an amorphous capping layer 3 nm in thickness where spatially modulated phase separation is initiated. It is shown that the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 12 publications
2
27
0
Order By: Relevance
“…Chen et al reported that SD can be induced by ion-impingement during the deposition of amorphous TiC thin films by pulsed DC magnetron sputtering. They also found that the energy flux of impinging ions enhances the diffusion coefficient [15]. They have tentatively expressed ion-impingement-enhanced diffusion coefficient as [15,17]
10.1080/14686996.2018.1482520-F0006Figure 6.Phase separation in Mn ferrite films as a function of the growth temperature and magnetic field applied during the film growth.
…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Chen et al reported that SD can be induced by ion-impingement during the deposition of amorphous TiC thin films by pulsed DC magnetron sputtering. They also found that the energy flux of impinging ions enhances the diffusion coefficient [15]. They have tentatively expressed ion-impingement-enhanced diffusion coefficient as [15,17]
10.1080/14686996.2018.1482520-F0006Figure 6.Phase separation in Mn ferrite films as a function of the growth temperature and magnetic field applied during the film growth.
…”
Section: Resultsmentioning
confidence: 99%
“…They also found that the energy flux of impinging ions enhances the diffusion coefficient [15]. They have tentatively expressed ion-impingement-enhanced diffusion coefficient as [15,17]
10.1080/14686996.2018.1482520-F0006Figure 6.Phase separation in Mn ferrite films as a function of the growth temperature and magnetic field applied during the film growth. Red open circles, green crossed circles, and black crosses indicate that the phase separation was confirmed, initiated, and not observed, respectively.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Spontaneous superlattice formation is also reported for metal alloy (Au-Ni) and carbide (TiC) thin films deposited under an ion-impingement (bombardment) atmosphere. 9,10 In their works, additional kinetic energy by ion-impingement is regarded as having a lower activation energy of up-hill diffusion, which is characteristic of spinodal decomposition. For oxides, few reports describe spontaneous superlattice formation during thin film deposition.…”
Section: Introductionmentioning
confidence: 99%